Practical Guide to MOC: Who, What, When, Why, and How. (23rd August 2013) - Teng, Marita S.; Malekzadeh, Sonya; Miller, Robert H.; Choi, Sukgi S.; Lin, Derrick T.; Weber, Randal S.; Smith, Shane
Abstract : Program Description: This miniseminar is designed to assist American Board of Otolaryngology (ABOto) diplomates in understanding the process of Maintenance of Certification (MOC). Panelists will include representatives from the American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS) and ABO to, as well as recent examinees of Part III MOC. Discussion will include the purpose, layout, and timeline of MOC, as well as practical tips for completing the requirements and passing the Part III examination. The panelists will also review what educational resources are available for continuation of lifelong learning, maintenance of certification, and recertification. The miniseminar will conclude with an interactive question and answer session. Educational Objectives: 1) Recognize MOC as a 10‐year cycle and understand the specific requirements for each of the four components of MOC. 2) Identify common concerns, anxieties, and misconceptions of Part III MOC. 3) List AAO‐HNS educational resources designed for lifelong learning, maintenance of certification, and recertification.